Transportation of entropy optimization in radiated chemically dissipative flow of Prandtl–Eyring nanofluid with activation energy. (February 2020) - Qayyum, Sumaira; Hayat, Tasawar; Kanwal, Mehreen; Alsaedi, Ahmed; Ijaz Khan, M.
Highlights: Entropy generation with Joule heating, activation energy, viscous dissipation and nonlinear thermal radiation is discussed. Higher Deborah number have reverse effect on temperature and concentration when compared with velocity. Larger Deborah number decays fluid velocity while temperature and concentration are enhanced. Temperature and concentration of fluid are enhanced for thermophoresis parameter. Concentration and temperature for Brownian motion have reverse effect. Entropy generation enhances for larger Deborah, Hartmann and Brinkman numbers while Bejan number has opposite effects. Abstract: Background: There are frequent strategies to enhance the efficiency of heat transport. Some strategies are employed of extended surfaces, utilization of vibration to the heat transport surfaces, and use of small scale channels. Efficiency of heat transport can also be enhanced by intensifying the thermal conductivity of working material. Engine oil, water and ethylene glycol are frequently utilized for heat transport liquids having comparatively low thermal conductivities then solids. Thermal conductivity of solids can be employed to improve the thermal conductivity of fluid through addition of nano or micro type solid particles to that liquid. The viability of usage of such materials with sizes 2 µm or millimeters was recently scrutinized by numerous engineers and analyst. In this communication, we aim to analyze flow of non-Newtonian nanomaterial (Prandtl–Eyring nanofluid). Features of nanofluid discussed with Brownian and thermophoresis diffusion. Entropy generation, thermal radiation, dissipation, activation energy, Joule heating and radiative heat flux is discussed. Method: Homotopic convergent solutions are developed by using OHAM. Governing nonlinear equations are developed. Results and conclusion: Fluid variable has opposite behavior on temperature and velocity. For larger thermophoresis parameter, temperature and concentration are increased. Concentration is reduced by improving Brownian motion parameter while temperature increases. Entropy generation improves with larger fluid parameter and Brinkman number, while Bejan number has opposite effect.